The role of catechol-o-methyltransferase in postpartum depression - Dewi, Indah Kusuma; Natasia, Caroline Putri; Gunadi, Julia Windi; Sanjaya, Ardo (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
The global prevalence of postpartum depression is increasing annually. This condition has been associated with polymorphisms in the catechol-O-methyltransferase (COMT) enzyme, which plays a critical role in the degradation of catecholamines. Therefore, a literature review was conducted to examine the influence of COMT enzyme variants on postpartum depression, with a focus on specific time periods and genetic variants implicated in the disorder. The review methodology involved a systematic search of articles on the PubMed database using the keywords